1962
DOI: 10.1103/physrev.127.2192
|View full text |Cite
|
Sign up to set email alerts
|

Total Neutron Cross Section ofPb208

Abstract: Measurements are reported on the total neutron cross section of isotopically enriched Pb 208 (99.75%) for neutron energies in the range from 720 to 1890 keV with an energy spread of about 3 keV. In this region at least 85 resonances are observed, of which 24 are analyzed to give tentative spin assignments and reduced widths. The reduced-width estimates furnish evidence that the J = 5/2 resonances at 723 and 821 keV have even parity. Differential cross sections of normal lead measured with 50-keV energy spread … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Experimental data are taken from Refs. [46][47][48][49][50][51][52][53][54][55][56][57]. 208 Pb, the first and second columns display the results from Ref.…”
Section: Dispersive Spherical Optical Model Potentialmentioning
confidence: 99%
“…Experimental data are taken from Refs. [46][47][48][49][50][51][52][53][54][55][56][57]. 208 Pb, the first and second columns display the results from Ref.…”
Section: Dispersive Spherical Optical Model Potentialmentioning
confidence: 99%
“…For large resonances, Fowler et al [24] reported parameters up to 1.87 MeV. As this nucleus is important (because it is doubly magic) in nuclear physics, we analyze four s-wave resonances below 1.8 MeV as shown in Table VII.…”
Section: Pb S-wave Resonancesmentioning
confidence: 99%
“…In contrast to these studies, an analysis of n-208Pb total cross section data near 1 MeV [4] by Satkowiak et a1 [5] suggested a linear energy dependence for the volume integral of the real optical potential. Recently Schutt et ul [6], who analysed n-208Pb data from 2-250 MeV, also found a linear energy dependence for this parameter at low energies.…”
mentioning
confidence: 90%
“…The present study is a phenomenological analysis of n-'08Pb total cross section data [3][4][5][6][13][14][15] over the energy range 1-14 MeV. We employ a new method of analysis at a, gross structure extrema and include recently reported high resolution n-*'*Pb data [3, 141. Unlike the case for analyses which include differential cross section data [2,3,[7][8][9][10][11], at the low energies of interest here total cross section analyses have the distinct advantages that no corrections for compound nucleus effects are required and that meaningful analyses can be made below 4 MeV neutron energy, where pronounced structure exists.…”
mentioning
confidence: 99%